Risk Management among Department of Tourism-Accredited Hotels in Region VIII - Dadulla, Daffodel M.; Cabatingan, Albim Y.; Delantar, Alexander Franco A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
he study assessed the risk management implementation and the degree of likelihood and severity of risks affecting the Department of Tourism-Accredited hotels in Region VIII. In addition, it took into account if there is a significant difference between the perspectives of middle management and rank-and-file employees and the significant relationship of risk management implementation and likelihood and severity of risks and its facilitating and impeding factors. To attain these, the study utilized both quantitative framework through survey and a qualitative method through interview. Sixteen hotels participated the study. Overall, establishments demonstrated an implemented category yet presence of variability suggests the need for continuous improvement in implementation. As to likelihood and severity of risks it is perceived as “unlikely to happen” yet “very severe” suggesting to roll-out proactive measures. It showed significant difference in viewpoints where the middle management have a better grasps of risk management than the rank-and-file employees. While for the test of significant relationship it has a clear negative correlation while no significant correlation was found between risk management and severity of risks. It revealed themes reactive approach rather than proactive risk management where these hotels need to embody a culture of proactive culture, employee education and training, budget allocation and get rid of being resistance to change and lack of cooperation to enhanced strategies to risk management. Based on the findings, a comprehensive risk management plan anchored to ISO 31000-2018 will be helpful to lessen the vulnerability to various risks to safeguard its stakeholders especially it guests.